The upstarts how Uber, Airbnb, and the killer companies of the new Silicon Valley are changing the world - Brad Stone (New York Little, Brown and Company, 2017)
Ten years ago, the idea of getting into a stranger's car, or walking into a stranger's home, would have seemed bizarre and dangerous, but today it's as common as ordering a book online. Uber and Airbnb have ushered in a new era: redefining neighborhoods, challenging the way governments regulate business, and changing the way we travel. In the spirit of Silicon Valley renegades like Steve Jobs and Bill Gates, another generation of entrepreneurs is using technology to upend convention and disrupt entire industries. Led by people like Travis Kalanick of Uber and Brian Chesky of Airbnb, they are rewriting the rules of business and often sidestepping serious ethical and legal obstacles in the process. The Upstarts is the story of two new titans of business and a dawning age of tenacity, conflict, and wealth. In Brad Stone's account of the most radical companies of the new Silicon Valley, we discover how it all happened.
Includes bibliographical references and an index
Keywords: Airbnb (Firm)